ELF-AWARENESS AND INTERCULTURAL COMMUNICATIVE COMPETENCE IN ELT POLICIES IN PORTUGAL - Guerra, Luís (Estudos Linguísticos e Literários, 2020)
This study attempts to examine to what extent the concepts of Intercultural Communicative Competence and English as a Lingua Franca are theoretically and practically formulated in some of the most recently implemented European and Portuguese English language teaching documents and, if so, how they are framed to be put into practice in the English language classroom. Overall, the documents analyzed—the Common European Framework of Reference for Languages (2001), the CEFR Companion Volume with New Descriptors (2018), both published by the Council of Europe, and the Essential Learnings (2018), introduced by the Portuguese Ministry of Education—display traditional approaches to the development of intercultural (communicative) competence in the English language classroom failing to truly and consistently represent the current role of English as an international lingua franca.